Viral - Cook, Robin, 1940- (G.P. Putnam's Sons, 2021)
"In this electrifying new medical thriller from New York Times bestseller Robin Cook, a family's exposure to a rare yet deadly virus puts them at the center of a terrifying danger to mankind--and pulls back the curtain on a healthcare system powered by greed and corruption"--